Effects of Thermal and Pressure Histories on the Chemical Strengthening of Sodium Aluminosilicate Glass - Svenson, Mouritz N.; Thirion, Lynn M.; Youngman, Randall E.; Mauro, John C.; Bauchy, Mathieu; Rzoska, Sylwester J.; Bockowski, Michal; Smedskjaer, Morten M. (Frontiers in Materials, 2016)
Glasses can be chemically strengthened through the ion exchange process, wherein smaller ions in the glass (e.g., Na+) are replaced by larger ions from a salt bath (e.g., K+). This develops a compressive stress (CS) on the glass surface, which, in turn, improves the damage resistance of the glass. The magnitude and depth of the generated CS depends on the thermal and pressure histories of the glass prior to ion exchange. In this study, we investigate the ion exchange-related properties (mutual diffusivity, CS, and hardness) of a sodium aluminosilicate glass, which has been densified through annealing below the initial fictive temperature of the glass or through pressure-quenching from the glass transition temperature at 1 GPa prior to ion exchange. We show that the rate of alkali interdiffusivity depends only on the density of the glass, rather than on the applied densification method. However, we also demonstrate that for a given density, the increase in CS and increase in hardness induced by ion exchange strongly depends on the densification method. Specifically, at constant density, the CS and hardness values achieved through thermal annealing are larger than those achieved through pressure-quenching. These results are discussed in relation to the structural changes in the environment of the network-modifier and the overall network densification.